2006
DOI: 10.1523/jneurosci.3882-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Cytosolic Domains of sorLA/LR11 with the Amyloid Precursor Protein (APP) and β-Secretase β-Site APP-Cleaving Enzyme

Abstract: sorLA is a recently identified neuronal receptor for amyloid precursor protein (APP) that is known to interact with APP and affect its intracellular transport and processing. Decreased levels of sorLA in the brain of Alzheimer's disease (AD) patients and elevated levels of amyloid-␤ peptide (A␤) in sorLA-deficient mice point to the importance of the receptor in this neurodegenerative disorder. We analyzed APP cleavage in an APP-shedding assay and found that both sorLA and, surprisingly, a sorLA tail construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(140 citation statements)
references
References 43 publications
3
135
0
1
Order By: Relevance
“…Spoelgen et al (36) previously identified a binding site in the cytoplasmic tail. We speculate that the use of different cell lines (SH-SY5Y cells in our study versus N2a cells by Spoelgen et al (36)) may explain why we see no interaction between the cytoplasmic tails.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spoelgen et al (36) previously identified a binding site in the cytoplasmic tail. We speculate that the use of different cell lines (SH-SY5Y cells in our study versus N2a cells by Spoelgen et al (36)) may explain why we see no interaction between the cytoplasmic tails.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that SorLA-⌬CR did not decrease the processing of APP, providing strong evidence of a specific role for SorLA in determining the intracellular trafficking and fate of APP. However, SorLA has also been shown to bind BACE (36), and it is therefore possible that APP and BACE compete for binding to the same region of SorLA. Thus, our mutants may also affect the ability to bind and sort BACE, although we believe that APP is the preferred binding partner of SorLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It further acts as a switch for substrate specificity of ␥-secretase because notch cleavage is, in contrast to APP ␥-cleavage, not affected. It has been shown recently that other proteins involved in protein transport, including syntaxin1a (Khvotchev and Sudhof, 2004) and LR11/sorLA (Scherzer et al, 2004;Andersen et al, 2005;Spoelgen et al, 2006), can impact APP processing. Recent data from BACE transgenic mice also support the idea that the location of BACE, even more so than the amount of BACE in a cell, influences A␤ generation (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of SorLA with the retromer mediates the recycling of APP from endosome to TGN, precluding the preferential  cleavage in endosome. Downregulation of SorLA enhances A formation in cultured cells and in mouse AD models [34,35] . The level of SorLA is reduced in sporadic AD patients, indicating that SorLA may play important roles in A production and AD pathogenesis.…”
Section: Protein Interactionmentioning
confidence: 98%